Prove it ...........
Attachments:
![](https://hi-static.z-dn.net/files/ddc/b14dd6846b49cc53c3485eb1acd5801c.jpg)
Answers
Answered by
1
Step-by-step explanation:
LHS = √(1+cosA)/√(1-cosA)
= Multiply the numerator & the denominator by √(1+cosA)
= √(1+cosA)² / √(1 - cos)(1+cosA)
= (1+cosA) / √(1-cos²A)
= (1+cosA) / √(sin²A)
= (1 + cosA) / sinA
= (1/sinA) + (cosA/sinA)
= cosec A + cot A = RHS
Hence Proved that LHS = RHS
Answered by
0
Answer:
hope helpful please follow me
Attachments:
![](https://hi-static.z-dn.net/files/dba/935b68c505626a97027c47940e953d71.jpg)
Similar questions